Penerapan Dasa Darma Pramuka dalam Kehidupan Sehari-Hari Siswa SDN Sawojajar 4 - Nur Anifi Khusnul Chotimah; Yuris Indria Persada (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2025)
The moral crisis among the younger generation, such as a lack of caring, social ethics, as well as dishonest and undisciplined attitudes, shows the need for stronger character education. One of the efforts made is through Scout education, which aims to shape students' character through the application of Dasa Darma as a guide to life. This research aims to analyze the character values in Dasa Darma which are implemented at SDN Sawojajar 4, Malang City, as well as the impact of implementing a reward system in increasing students' motivation to apply these values in everyday life. The methods used include observation, interviews and documentation, with a descriptive qualitative approach. The research results show that Dasa Darma is effective in instilling positive moral values such as honesty, mutual cooperation, discipline and responsibility in students. The reward system has been proven to be able to motivate students to behave positively in accordance with the values of Dasa Darma. These results support social learning theory which states that individuals tend to learn through observation and imitation of models. In conclusion, the application of Dasa Darma through Scout activities has a significant impact on the formation of students' character, thereby helping to overcome the moral crisis of the younger generation and preparing them as individuals who are useful for society and the nation.